DAYA DUKUNG LINGKUNGAN PERAIRAN KECAMATAN MANTANG KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU UNTUK KEGIATAN BUDIDAYA IKAN DALAM KERAMBA JARING APUNG (Jurnal Kajian Lingkungan, 2014)
Observations were conducted during four months from November 2013 to February 2014 to determine the carrying capacity of Mantang Sub district waters for aquaculture activities based on the parameters of physics, chemistry and plankton abundance as bio indicators and estimate the impact on economy and ecology in the development of aquaculture in coastal areas. The sources of data in this research were obtained from the determination of sampling locations for 6 stations, the analysis of waters existing was carried out by the measurement of physical, chemical and biological parameters as well as the carrying capacity for floating net cages with phosphorus method.The analysis results of waters environmental existing of Mantang sub district are still in good condition that is adapted to Government Regulation No. 51/2004 where the parameters of temperature, pH and DO still below the Quality Standard but for Phosphate parameter have shown an alarming condition. Stations that can not be developed for aquaculture activity are Mantang baru Island, Pasir Merah Island and Alang Island. While the calculation of the waters environmental carrying capacity of Mantang sub district is still able to accommodate 650 units of cage.Keywords : Carrying Capacity, Phosphorus Method, Aquaculture Activities